Hypovitaminosis D is associated with increased whole body fat mass and greater severity of non‐alcoholic fatty liver disease. (1st October 2013) - Dasarathy, Jaividhya; Periyalwar, Pranav; Allampati, Sanath; Bhinder, Vikram; Hawkins, Carol; Brandt, Patricia; Khiyami, Amer; McCullough, Arthur J.; Dasarathy, Srinivasan
Abstract Background & Aims Hypovitaminosis D is common in obesity and insulin‐resistant states. Increased fat mass in patients with non‐alcoholic fatty liver disease (NAFLD) may contribute to hypovitaminosis D. To determine the relation among plasma vitamin D concentration, severity of disease and body composition in NAFLD. Methods Plasma vitamin D concentration was quantified in 148 consecutive biopsy‐proven patients with NAFLD (non‐alcoholic steatohepatitis – NASH: n = 81; and hepatic steatosis: n = 67) and healthy controls (n = 39). NAFLD was scored using the NASH CRN criteria. Body composition was quantified by bioelectrical impedance analysis and abdominal CT image analysis. Results Plasma vitamin D concentration was significantly lower in NAFLD (21.2 ± 10.4 ng/ml) compared with healthy controls (35.7 ± 6.0 ng/ml). Higher NAFLD activity scores were associated with lower plasma concentration of vitamin D (r2 = 0.29; P < 0.001). Subgroup analysis among patients with NAFLD showed that patients with NASH had significantly lower (P < 0.01) vitamin D levels than those with steatosis alone (18.1 ± 8.4 vs. 25.0 ± 11.3 ng/ml). Low concentrations of vitamin D were associated with greater severity of steatosis, hepatocyte ballooning and fibrosis (P < 0.05).On multivariate regression analysis, only severity of hepatocyte ballooning was independently associated (P = 0.02) with low vitamin D concentrations. Plasma vitamin D (P = 0.004) and insulin concentrations (P = 0.03) were independent predictors of the NAFLD activity score on biopsy. Patients with NAFLD had higher fat mass that correlated with low vitamin D (r2 = 0.26; P = 0.008). Conclusions Low plasma vitamin D concentration is an independent predictor of the severity of NAFLD. Further prospective studies demonstrating the impact of vitamin D replacement in NAFLD patients are required.